2009
DOI: 10.33151/ajp.7.4.185
|View full text |Cite
|
Sign up to set email alerts
|

Protective Jurisdiction, Patient Autonomy and Paramedics: The Challenges of Applying the Nsw Mental Health Act

Abstract: Paramedics form part of the frontline response to mental health care in the community. Changes to mental health laws across the country have seen an increase in the role and responsibilities paramedics have in assessing, treating and managing mental health patients. The increasing complexity of the paramedic role associated with these changes requires a clear understanding of the legal, ethical and organisational requirements that accompany them. This paper will examine the relevant legislative princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Another explanation for this finding is that inadequate undergraduate and in-service mental health education and training constrained paramedics’ confidence, ability and willingness to engage therapeutically with patients with mental health and/or AOD problems [2, 5, 9, 1114]. A third explanation is high workloads and pressure from paramedic services to be available to respond to waiting cases precluded a desire to broaden their existing scope of practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for this finding is that inadequate undergraduate and in-service mental health education and training constrained paramedics’ confidence, ability and willingness to engage therapeutically with patients with mental health and/or AOD problems [2, 5, 9, 1114]. A third explanation is high workloads and pressure from paramedic services to be available to respond to waiting cases precluded a desire to broaden their existing scope of practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several other contextual factors beyond paramedics’ individual attitudes have also been identified as potentially shaping their work practices in caring for patients with mental health and/or AOD problems. For instance, high work pressures and limited mental health training may constrain the ability of paramedics to respond to the needs of patients with these problems beyond transportation [2, 5, 9, 1114]. Alternatively, organisational cultures in ambulance services that promote a medical emergency care focus can, potentially, reinforce the idea of responding to non-medical emergency-related mental health and/or AOD presentations as being a less important aspect of paramedics’ role [2, 6].…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that limited education and training have impacted paramedics’ confidence and preparedness, resulting in varying views about their role [ 14 ]. Studies have demonstrated a link between inadequate education and training and knowledge of legislative responsibilities including issues with interpreting and applying the Mental Health Act [ 16 , 17 , 18 ]. Previous work investigating paramedics’ perception of education and training highlighted that paramedics felt inadequately prepared when attending to mental-health-related cases [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This training is geared towards dealing with mental illness in the emergency setting (26), which is the type of training that is pertinent for the purposes of emergency apprehension (27). It is reasonable to expect that authorised ACTAS advanced life support paramedics, who have received appropriate training and who have satisfied the chief officer (ambulance service) that they are competent to perform this function, will be more accurate than police in their assessment of whether a person has a mental illness (8). The existence of a mental illness or a mental disorder is one of the two criteria that must be satisfied before the power to apprehend is used.…”
Section: Actas Paramedics Are Better Qualified Than Police To Assess mentioning
confidence: 99%